2020
DOI: 10.1038/s41598-020-72132-1
|View full text |Cite
|
Sign up to set email alerts
|

Parvimonas micra as a putative non-invasive faecal biomarker for colorectal cancer

Abstract: The use of faecal microbial markers as non-invasive biomarkers for colorectal cancer (CRC) has been suggested, but not fully elucidated. Here, we have evaluated the importance of Parvimonas micra as a potential non-invasive faecal biomarker in CRC and its relation to other microbial biomarkers. The levels of P. micra, F. nucleatum and clbA + bacteria were quantified using qPCR in faecal samples from a population-based cohort of patients undergoing colonoscopy due to symptoms from the large bowel. The study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 31 publications
12
64
1
Order By: Relevance
“…to promote the formation of metastases [11,82]. F. nucleatum and P. micra are commonly enriched in CRC sections [83][84][85], and a recent microbiome study reported the enrichment of of vaginosis [101], suggesting a potential pathogenic role or an association with dysbiosis.…”
Section: Accepted Articlementioning
confidence: 99%
“…to promote the formation of metastases [11,82]. F. nucleatum and P. micra are commonly enriched in CRC sections [83][84][85], and a recent microbiome study reported the enrichment of of vaginosis [101], suggesting a potential pathogenic role or an association with dysbiosis.…”
Section: Accepted Articlementioning
confidence: 99%
“…Given the link between gut microbiota dysbiosis and CRC [ 21 ], microbial markers have recently emerged as a promising indicator in early CRC screening (cf Table 1 ). Known specific oncogenic gut bacteria have been assessed individually from both fecal and mucosal samples from patients with CRC, including strains of Bacteroides fragilis , Escherichia coli , Enterococcus faecalis , Streptococcus gallolyticus, and Fusobacterium nucleatum [ 16 , 17 , 21 , 22 , 23 , 24 , 25 ]. Over the last few years, many studies using sequencing methods with whole-genome shotgun (WGS) and/or 16S RNAr DNA sequencing have also highlighted several signatures (mostly in feces) between individuals with CRC and healthy control subjects [ 13 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Gut Microbiota Biomarker For Cancer Screeningmentioning
confidence: 99%
“…Differences were not affected when controlling for potential confounding by age, body mass index (BMI) or sex (40). These identified polymicrobial signatures could potentially be harnessed as screening biomarkers for CRC [ 25 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] (cf. Table 1 ).…”
Section: Gut Microbiota Biomarker For Cancer Screeningmentioning
confidence: 99%
“…On the other hand, other evidences suggested that some specific bacterium such as genus Parvimonas may cause the EGFR mutation. Currently, several evidences suggested that Parvimonas micra, a member of genus Parvimonas, was enriched in patients with colon cancer [68,69]. Interestingly, in vitro study demonstrated that infection of Parvimonas micra could enhance the ability of human inflammatory cells to generate reactive oxygen species and caused DNA damage of human cells [70], which could cause oncogene mutation and carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%